2014
DOI: 10.1021/ja508588b
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Chemoselective Carbonylation of Aminophenols with Iodoarenes: Alkoxycarbonylation vs Aminocarbonylation

Abstract: Palladium-catalyzed chemoselective carbonylation of aminophenols with iodoarenes was realized by changing ligand and base. 3- or 4-Aminophenols afforded esters in high yields and selectivities using 1,3-bis(diphenylphosphino)propane as the ligand and K2CO3 as the base, and gave amides in high yields and selectivities using 1,3-bis(diisobutylphosphino)propane as the ligand and DBU as the base. 2-Aminophenol only gave amides in high yields under both conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 52 publications
3
68
0
2
Order By: Relevance
“…and Heck et al., palladium‐catalyzed carbonylation, an efficient pathway for the constructing of carbonyl‐containing skeletons, has become a versatile tool in creating chemical diversity . Long‐lasting interests have been focused on the chemoselectivity of the palladium‐catalyzed carbonylation of one nucleophile bearing two nucleophilic sites (Scheme ), for example, the chemoselective carbonylation of aminophenols (alkoxycarbonylation vs. aminocarbonylation, Scheme a), the selective carbonylative synthesis of 1,3‐diketones and vinylbenzoates from ketones with α‐hydrogen atoms (carbonylative α‐arylation vs. O ‐benzoylation, Scheme b) and the base‐controlled tunable synthesis of linear‐ and angular‐fused quinazolinones with 2‐aminopyridine (two different nucleophilic nitrogen centers, Scheme c) …”
Section: Introductionmentioning
confidence: 99%
“…and Heck et al., palladium‐catalyzed carbonylation, an efficient pathway for the constructing of carbonyl‐containing skeletons, has become a versatile tool in creating chemical diversity . Long‐lasting interests have been focused on the chemoselectivity of the palladium‐catalyzed carbonylation of one nucleophile bearing two nucleophilic sites (Scheme ), for example, the chemoselective carbonylation of aminophenols (alkoxycarbonylation vs. aminocarbonylation, Scheme a), the selective carbonylative synthesis of 1,3‐diketones and vinylbenzoates from ketones with α‐hydrogen atoms (carbonylative α‐arylation vs. O ‐benzoylation, Scheme b) and the base‐controlled tunable synthesis of linear‐ and angular‐fused quinazolinones with 2‐aminopyridine (two different nucleophilic nitrogen centers, Scheme c) …”
Section: Introductionmentioning
confidence: 99%
“…[21] They found that the nature of the phosphine ligand played ak ey role in this reaction. [21] They found that the nature of the phosphine ligand played ak ey role in this reaction.…”
Section: Ligand-controlled Chemodivergent Carbonylationmentioning
confidence: 99%
“…Aniline and phenol derivatives have been widely used as nucleophiles in carbonylative transformations,t hus generating amides and esters,respectively.Xuand Alper investigated the chemoselective carbonylation of aminophenols with iodoarenes (Scheme 7). [21] They found that the nature of the phosphine ligand played ak ey role in this reaction. By employing 1,3-bis(diphenylphosphino)propane (DPPP) as the ligand and K 2 CO 3 as the base,c arbonylation of 3-and 4-aminophenols afforded the alkoxycarbonylation products, esters,i nh igh selectivities,w hereas amides could be synthesized selectively by using 1,3-bis-(diisobutylphosphino)propane (DIBPP) as the ligand and DBUa st he base.C ontrol experiments showed that ArCOPdX was the key intermediate,a nd the coordination abilities of NH 2 and OH to the palladium intermediate were critical for determining the reaction pathway.I ti sw ell known that the amino group is astronger nucleophile than the hydroxy group.T he presence of an electron-rich ligand favors attack of the amino group rather than the hydroxy group,t hus delivering the aminocarbonylation product.…”
Section: Ligand-controlled Chemodivergent Carbonylationmentioning
confidence: 99%
“…26 In general, with or without phosphine co-ligands present the active Rh-H species is formed efficiently from the reaction of aliphatic amines and the rhodium precursor complex. 26 In general, with or without phosphine co-ligands present the active Rh-H species is formed efficiently from the reaction of aliphatic amines and the rhodium precursor complex.…”
Section: Mechanistic Studiesmentioning
confidence: 99%